MENGENAL PEMASARAN DIGITAL DAN MARKET PLACE: Solusi Meningkatkan Penjualan di Masa Pandemi Covid-19 - Wahyudi Wahyudi; Mukrodi Mukrodi; Endang Sugiarti; I Nyoman Marayasa; Syamsi Mawardi (Jurnal PKM Manajemen Bisnis, 2022)
Today's in digital era, all sectors use technology to develop production and increase sales, including Micro, Small and Medium Enterprises. But in fact, many obstacles are faced, for example, existing human resources cannot use technology and information, the high cost of technology procurement, lack of references, and so on. The purpose of this Community Service activity is to provide additional knowledge to MSME actors in the South Tangerang Buaran Exit, about the use of digital marketing and digital markets, so that they can overcome the problem of declining sales due to the Covid-19 pandemic. The method of service activities is carried out by explaining the material and sharing experiences. In practice, exposure activities are carried out by displaying material in the form of slideshows, pictures, and videos. Meanwhile, the experience sharing session was carried out by showing directly how to do digital marketing in the digital market, such as how to register and open a digital store at Shopee, Tokopedia, Bukalapak, and so on. Then it is also explained, how to get competitive products from the marketplace. This activity was held for three days, Tuesday 05 October 2021 to 07 October 2021. Argumentatively the results of this activity became a reference for the participants on how to do business in the digital era. So that the participants gain knowledge, which makes them aware of the importance of adapting. In addition, this activity spurred the spirit of doing business with a new model, namely further optimizing online sales in the digital market.